Two Worlds of Distance Education: The Function of Access and Technology - Namin Shin (Adult Education Research Conference, 2000)
In order to further our understanding of distance education as a social practice, this roundtable session suggests two disparate semantic and geographic worlds of distance education: The world that sees distance education as the means to eliminate the barriers to learning opportunities imposed by societal structure, and the world that views distance education as a technology driven form of education.